LITERASI DIGITAL PENCEGAHAN CYBERBULLYING DI LINGKUNGAN SISWA SMP - Prihandini, Puji; Rachmaniar, Rachmaniar; Anisa, Renata (Universitas Negeri Malang, 2024)
LITERACY DIGITAL CYBERBULLYING PREVENTION IN THE STUDENT ENVIRONMENT JUNIOR HIGH SCHOOL The synergy report on the women's violence database, compiled by the Ministry of Women's Empowerment and Child Protection, indicates that the highest number of victims of violence, categorised by age, is within the teenage range, specifically 13-17 years old. One of the most prevalent forms of violence is cyber violence, which is commonly referred to as cyberbullying. Cyberbullying can be defined as the intimidation of an individual or group through digital technology. The relatively low digital literacy index in Indonesia may be a contributing factor to the continued prevalence of cyber violence in the country. One potential strategy for the prevention of cyberbullying is the promotion of digital literacy and its role in the prevention of such behaviour. A programme of counselling on digital literacy in the context of cyberbullying prevention was conducted at YPKP Middle School in Bandung City. The educational materials provided covered the development of social media, its characteristics, benefits, and impacts of using social media, as well as knowledge of cyberbullying, its impact, prevention, and how to deal with it. The results of these activities demonstrated that the majority of students already own mobile phones and that all students have access to social media. While the majority of students have heard the term cyberbullying, few are equipped with the necessary knowledge to respond effectively when they encounter or experience cyberbullying. Laporan sinergi database kekerasan terhadap perempuan yang disusun oleh Kementerian Pemberdayaan Perempuan dan Perlindungan Anak menunjukkan bahwa jumlah korban kekerasan tertinggi, yang dikategorikan berdasarkan usia, berada dalam rentang usia remaja, khususnya 13-17 tahun. Salah satu bentuk kekerasan yang paling banyak terjadi adalah kekerasan di dunia maya, yang biasa disebut dengan cyberbullying. Cyberbullying dapat didefinisikan sebagai intimidasi terhadap individu atau kelompok melalui teknologi digital. Indeks literasi digital yang relatif rendah di Indonesia dapat menjadi faktor yang berkontribusi terhadap prevalensi kekerasan siber yang terus meningkat di negara ini. Salah satu strategi potensial untuk pencegahan cyberbullying adalah dengan mempromosikan literasi digital dan perannya dalam pencegahan perilaku tersebut. Sebuah program penyuluhan tentang literasi digital dalam konteks pencegahan cyberbullying dilakukan di Sekolah Menengah Pertama YPKP di Kota Bandung. Materi penyuluhan yang diberikan meliputi perkembangan media sosial, karakteristik, manfaat, dan dampak dari penggunaan media sosial, serta pengetahuan tentang cyberbullying, dampak, pencegahan, dan cara mengatasinya. Hasil dari kegiatan ini menunjukkan bahwa mayoritas siswa telah memiliki telepon genggam dan semua siswa memiliki akses ke media sosial. Meskipun mayoritas siswa pernah mendengar istilah cyberbullying, hanya sedikit yang memiliki pengetahuan yang cukup untuk merespon secara efektif ketika mereka menemukan atau mengalami cyberbullying.